2017
DOI: 10.3892/ol.2017.5866
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Pro1170Ala polymorphism is associated with decreased survival rate in HER2-negative breast cancer

Abstract: Abstract. The Pro1170Ala polymorphism is one of the most common polymorphisms of human epidermal growth factor receptor 2 (HER2) and may affect the clinical outcome in breast cancer. Therefore, in the present study, the incidence of the HER2 Pro1170Ala polymorphism was determined in 3,305 female patients with operable primary breast cancer using a DNA-sequencing assay, and the potential association with survival was investigated. Of these 3,305 patients, 29% (955/3,305) were homozygous for the Pro/Pro genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Evidence have been accumulated on the role of ERBB2 amplification in cancer, while very little is known on the role of point mutations 23 . It was recently reported that patients with ERBB2-negative breast cancer with the Pro1170Ala polymorphism variant exhibit a decreased survival outcome 24 . Another study suggested that the Ala variant increased the risk of lung cancer, indicating that it may promote ERBB2 activity 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence have been accumulated on the role of ERBB2 amplification in cancer, while very little is known on the role of point mutations 23 . It was recently reported that patients with ERBB2-negative breast cancer with the Pro1170Ala polymorphism variant exhibit a decreased survival outcome 24 . Another study suggested that the Ala variant increased the risk of lung cancer, indicating that it may promote ERBB2 activity 25 .…”
Section: Discussionmentioning
confidence: 99%